PENINGKATAN HASIL BELAJAR PADA MATERI KALOR MENGGUNAKAN MODEL PREDICT, OBSERVE, DISCUSS, EXPLAIN - Theresia Widiani; Edy Tandililing; Hamdani Hamdani (Universitas Tanjungpura, 2020)
AbstractThe purpose of this research was to improve students learning outcomes of heat transfer material on Class VII SMP Negeri 2 Pontianak. The method conducted in this research was pre-experimental method with one-group pretest-postest research design. The sample of this research was Class VII A using Simple Random Sampling technique. The data of learning outcomes was conducted using 6 questions with multiple choices and 4 essay questions. The technique of data analysis conducted in this research was Wilcoxon Test. The conducted Wilcoxon Test showed that the sig. result was 0.000 (<0.05) which means there was such differences on students learning outcomes of science before and after learning. The improvement of students learning outcomes was 20.7 with learning effectiveness about 1.3 and categorized as high in improving students learning outcomes on Class VII A SMP Negeri 2 Pontianak, so it concluded that the use of Predict, Observe, Discuss, Explain (PODE) learning model could improve the students learning outcomes on heat transfer material.Keywords: Learning Outcomes, Heat Transfer, PODE Model